2018
DOI: 10.3382/ps/pey247
|View full text |Cite
|
Sign up to set email alerts
|

Copper and zinc sources and levels of zinc inclusion influence growth performance, tissue trace mineral content, and carcass yield of broiler chickens

Abstract: A 35-d experiment was conducted in broilers to study the effect of supplementation of sulfate or hydroxychloride forms of Zn and Cu at 2 supplemental Zn levels on growth performance, meat yield, and tissue levels of Zn. On day 0, 900 male Ross 308 broiler chicks (45 ± 1.10 g) were allocated to 4 treatments in a randomized complete block design and 2 × 2 factorial arrangement of treatments. The factors were 2 sources (sulfate or hydroxychloride) of Zn and Cu and 2 levels (low or high) of Zn. The Zn sources were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
75
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(89 citation statements)
references
References 40 publications
10
75
4
Order By: Relevance
“…Therefore, in the present study, copper acetate (CA), an organic source of copper, curcumin (CR), and a mixture of curcumin with copper acetate (CA-CR), were evaluated. Selection of CA was based on its advantages over inorganic sources since it has been described that inorganic sources tend to dissociate in the upper part of the gastrointestinal tract, causing a decrease in the availability of copper due to its interaction with other metals (chelation) and therefore a reduction in its activity [18,43]. In contrast, the solubility of organic sources of copper is higher in weak acid enviroments, making their dissolution slower and increasing their availability and activity [43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, in the present study, copper acetate (CA), an organic source of copper, curcumin (CR), and a mixture of curcumin with copper acetate (CA-CR), were evaluated. Selection of CA was based on its advantages over inorganic sources since it has been described that inorganic sources tend to dissociate in the upper part of the gastrointestinal tract, causing a decrease in the availability of copper due to its interaction with other metals (chelation) and therefore a reduction in its activity [18,43]. In contrast, the solubility of organic sources of copper is higher in weak acid enviroments, making their dissolution slower and increasing their availability and activity [43].…”
Section: Discussionmentioning
confidence: 99%
“…Selection of CA was based on its advantages over inorganic sources since it has been described that inorganic sources tend to dissociate in the upper part of the gastrointestinal tract, causing a decrease in the availability of copper due to its interaction with other metals (chelation) and therefore a reduction in its activity [18,43]. In contrast, the solubility of organic sources of copper is higher in weak acid enviroments, making their dissolution slower and increasing their availability and activity [43]. Furthermore, lower fecal copper excretion rates have been reported in broilers exposed to an organic source of copper compared to inorganic sources [44].…”
Section: Discussionmentioning
confidence: 99%
“…Although there was no difference between CTM50 and CTM100 groups on production performances, only the CTM100 diet increased EPI during the overall growth period compared with equal levels of TM from ITM treatment, which indicated that the complete substitution of inorganic TM sources by CTM could be as an alternative way to improve productive performance. This improvement in broiler performance appears to con rm the improved bioavailability of TM from organic sources [2,9,22]. However, other researchers have reported variable responses with the addition of organic TM on growth performance.…”
Section: Discussionmentioning
confidence: 70%
“…It is also known that Zn is essential for several microbes (Gielda and DiRita, 2012), indicating that a different source and level of Zn available in the gut may in uence the microbiota. Olukosi et al (2018) already showed a bene cial effect of HTM on growth performance and carcass quality in broiler chickens. The objective of the present study was to investigate the effects on growth performance, carcass and breast meat yield, and microbiota of broiler chickens fed STM or HTM in high and low Zn dosages.…”
Section: Introductionmentioning
confidence: 98%